Biodisponibilidade de fósforo e potássio provenientes de fertilizantes mineral e organomineral - Teixeira, Welldy Gonçalves (2013)
Phosphorus (P) and potassium (K) liberation and their availability to plants from an organomineral fertilizer were evaluated in two experiments at the Universidade Federal de Uberlândia, in Uberlândia, MG. The first one was done in 200-L plastic containers, cultivating sugar-cane seedlings in a Dystrustox. Treatments consisted of two sources and three doses of N, P2O5 and K2O, plus an additional treatment, with no fertilizer. The sources were: mineral fertilizer 4-20-20 and organomineral fertilizer 2-10-10 applied, for comparison purposes, in two different doses to supply the same amount of nutrients. Soil samples of the top 0-0,2 m layer were collected 133 days and 276 days after treatment application (DAA) to determine the contents of P, remaining P and K. Extraction of available P was done with two extractors: Mehlich-1 and ion exchange resin. The plants were harvested 231 days after seedling transplanting to the containers, evaluating the following characteristics: content and accumulation of P and K, dry matter, stalk production, sugar yield and technological variables. Resin presented greater P extraction capacity in the two soil sampling dates in relation to Mehlich- 1, which failed to detect available P content for plants. The analysis of remaining P revealed that, with time and with the organomineral fertilizer, less P adsorption occurred by the soil. This fertilizer was more effective in the doses applied, and can substitute the mineral fertilizer, presenting up to 15% greater efficacy in sugar-cane stalk production. Potassium mobility in the soil profile, as a function of soil texture and nutrient source, was evaluated in the second experiment. The test was done in leaching columns, using two soils (Dystrustox), a clayey texture and a medium one. The following sources were applied, in doses equivalent to 1500 kg ha-1 K2O: (a) mineral fertilizer 20-5-20 with soluble KCl; (b) organomineral fertilizer 16-1-16; (c) organomineral fertilizer 8-1-8, beside a control treatment, with no fertilization. Water was applied for 60 days in amount equivalent to 1.146 mm rainfall. At the end of this period, exchangeable K was determined in eleven soil layers of the column and also, the total amount of K in the leachate solution. Organomineral fertilizer resulted in greater amount of exchangeable K in top layers of both soils. Exchangeable K contents were not different among the fertilizers in deeper soil layers, except for two layers of the clayey soil, in which the contents of this element were greater with the mineral fertilizer. Losses by leaching depended on fertilizer type, with greater total amounts of K in the leachate solution in the treatment receiving mineral fertilizer.